ANALYSIS OF CLASS ACTION DECISION NUMBER 26/PDT.G/2009 /PN. TPI CONCERNING MARINE POLLUTION ON THE MINING BUSINESS AGENCY - Itok Dwi Kurniawan; Ferren Andhika; Devi Lestari; Dewi Indra Rosidah; Dilla Veranita (Jurnal Hukum Replik, 2020)
The sea is an important resource, especially for coastal communities. Therefore we are obliged to preserve and keep it from being damaged. If there is damage caused by human activity, what is harmed is humans and living creatures in the sea that will feel the loss. In exchange, the perpetrator of the damage must be punished. Environmental law enforcement has regulated all forms of violations or crimes committed by individuals or a body. Enforcement can be preventive (prevention) or by taking action (repressive). Actions are carried out based on consideration. These actions include Class Action Lawsuits, Criminal Actions, and Administrative Actions.Keywords: Class Action Lawsuits, Criminal Actions, and Administrative Actions.